PERALIHAN TRANS-ASIA PASIFIC PARTNERSHIP (TPP) MENJADI COMPREHENSIVE AND PROGRESSIVE AGREEMENT FOR TRANS-PACIFIC PARTNERSHIP (CPTPP) PASCA MUNDURNYA AMERIKA DARI KEANGGOTAAN - Yovana, Kesi; Nawartama, Fakhri (Moestopo Journal of International Relations (MJIR), 2025)
This research discusses the transition from the Trans-Asia Pacific Partnership to a comprehensive and progressive agreement on the Trans-Pacific Partnership after the departure of the United States. The United States, which was the original signatory to the Trans Asia – Pacific Partnership agreement, simply withdrew when Donald Trump led the United States. The withdrawal of the United States raises questions considering the benefits that will be gained from the Trans-Asia  Pacific Partnership agreement. International organization theory will explain the evolution of the transition from the Trans-Asia Pacific Partnership to a comprehensive and progressive agreement on the Trans-Pacific Partnership after the departure of the United States. Meanwhile, the method used in this research is descriptive qualitative which presents an in-depth picture of the social situation and describes the case clearly.